Predicting the Level of The Effect of High and Low Humidity Levels on The Saturation of Hemoglobin With Oxygen According To Some Physical, Functional Variables And The Accuracy Of Scoring For Football Players (A Comparative Study) - Mohammad (PhD.), Majed Sabar; Mohammed (M.A.), Ali Sabar; Al-kaabi (PhD.), Emad Kadhim Abd (International Journal of Psychosocial Rehabilitation, 2020)
There is no doubt that climate changes (the level of air humidity) have a clear impact, directly or indirectly, on the level of performance of players in general and football players in particular. Since the football game spends the interest of most people, it was necessary to search hardly to raise the level of its performance and its development. The importance of research lies in knowing the effect of humidity in different degrees (high humidity or saturated with humidity, low humidity or dry) at the level of hemoglobin saturation (Hb) sports body with oxygen (2O) through prediction according to physical and functional variables and accuracy of scoring for the player Football. The researchers used a descriptive method. The comparison method is appropriate to solve the research problem. The number of the research community reached (22) players. After that, the sample was chosen in a simple random way (lots) and their number was (10) players after excluding (4) players for use in the exploratory experiment. The researchers used the SPSS statistical system to extract the results of the tests. The most important conclusions are: (1) The adaptation of the wet climates exercises increases the ability of functional devices to perform in dry climates, (2) It was found that the higher the humidity of the air, the higher the body temperature after performing physical exertion and consequently the increased heart rate and breathing and the cause of fatigue of the players of the research sample. The most important recommendations are: (1) The necessity of training the players in the atmosphere of hypoxia, such as high humidity, for example, to increase the development of the work of the functional devices in anticipation of sudden climatic climates during the game. For players.